Comparative study of seismic design for different bridges structures - Naser, Ali Fadhil (Penerbit Universiti Kebangsaan Malaysia, 2022)
The main objective of this study is to compare the structural members capacity between different types of bridges structures under seismic load. The results of seismic modal analysis showed that the models of box girder bridge, precast T girder bridge, and U steel girder bridge had the higher values of natural frequency comparing with others bridges structures under seismic load. Pushover analysis in transvers direction showed that bent No. 2 of bridges structures which was located in the middle of bridges superstructure was displaced in transvers direction more than bent No. 1 and bent No. 3. In longitudinal direction, Precast I girder bridge had higher value of longitudinal displacement comparing with others bridges structures, and it was more than the maximum value of transvers displacement. The results of demand and capacity ratio showed that bent No. 2 was the critical structural member which had values of demand/capacity ratio more than 1.0 or near from it especially precast I girder bridge, precast T girder bridge, and U steel bridge, indicating that these types of bridges will be subjected to failure in bent No. 2. Therefore, there was needing to redesign the bents of these types of bridges by increasing the numbers of piers, using high strength materials in construction of bents, and increasing of dimensions of piers and pier caps. The results of internal forces showed that bent No. 2 was subjected to the maximum values of axial force, horizontal shear, and bending moment for all types of bridges structures. Also, it can be seen that the models of precast I girder bridge, precast T girder bridge, and U steel bridge had the higher values of forces comparing to others models, indicating that these results agree with results of demand/capacity ratio and pushover analysis method.